2015
DOI: 10.2174/1389203716666150213160438
|View full text |Cite
|
Sign up to set email alerts
|

Glucosidase II and MRH-Domain Containing Proteins in the Secretory Pathway

Abstract: N -glycosylation in the endoplasmic reticulum (ER) consists of the transfer of a pre-assembled glycan conserved among species (Glc3Man9GlcNAc2) from a lipid donor to a consensus sequence within a nascent protein that is entering the ER. The protein-linked glycans are then processed by glycosidases and glycosyltransferases in the ER producing specific structures that serve as signalling molecules for the fate of the folding glycoprotein: to stay in the ER during the folding process, to be retrotranslocated to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 157 publications
(223 reference statements)
0
17
0
Order By: Relevance
“…GI is associated to the Sec61 αβγ translocon complex, ensuring the removal of the outermost glucose almost immediately after transfer of the N ‐glycan [10]. The α1,3‐exoglucosidase GII is an ER‐resident soluble heterodimer composed by a catalytic subunit (GIIα) non‐covalently bound to the GIIβ subunit [11–13]. GIIα displays the (G/F)(L/I/V/M)WXDMNE consensus sequence typical of glycosylhydrolase family 31.…”
Section: The Er Glucosidasesmentioning
confidence: 99%
“…GI is associated to the Sec61 αβγ translocon complex, ensuring the removal of the outermost glucose almost immediately after transfer of the N ‐glycan [10]. The α1,3‐exoglucosidase GII is an ER‐resident soluble heterodimer composed by a catalytic subunit (GIIα) non‐covalently bound to the GIIβ subunit [11–13]. GIIα displays the (G/F)(L/I/V/M)WXDMNE consensus sequence typical of glycosylhydrolase family 31.…”
Section: The Er Glucosidasesmentioning
confidence: 99%
“…The γ subunit contains an MRH (mannose-6-phosphate receptor homology) domain similar to those found in ER glucosidase II (16). Since many MRH domains act as lectins that bind both M6P modified and non-modified high mannose oligosaccharides, its presence in the γ subunit suggests that it might facilitate subunit ability to bind the N-glycans of hydrolases, thereby modulating the αβ’s recognition capability (17). It was also suggested that the MRH domain binds glycans on the α subunit, but a recent study demonstrated that interaction between the αβ and γ subunits is MRH-independent (18).…”
Section: Introductionmentioning
confidence: 99%
“…Gls2 plays a key role in quality control of glycoprotein folding in ER, andis also responsible for the removal of the glucose added by UGGT. Cycles of deglucosylation and reglucosylation catalyzed by the opposing activities of UGGT and Gls2 continue until the glycoproteins acquire their native structure [15]. …”
Section: Introductionmentioning
confidence: 99%